Lora-Based Communication System using Artificial Intelligence for Monitoring Water Quality in Laguna Lake / Pereira, Gabrielle F.... [et al.]. - Pereira, Gabrielle F.; Cruz, Carl Manuel R.; Dulce, John Matthew D.; Mendoza, Tedio Kirby C.; FRANCISCO B. CULIBRINA (2024)
This study presents the development and implementation of a LoRa-based communication system integrated with artificial intelligence for real-time monitoring of water quality in Laguna Lake. The research addresses the growing concern over water pollution and the need for efficient monitoring solutions to safeguard the ecological health of the lake. The LoRa-Based Communication System using Artificial Intelligence to monitor water quality in Laguna Lake, a cooperative work of upright and curious student, has been successfully developed. The system contains Arduino Nano and ESP32 as a microcontroller to control the sensors, and a LoRa to transmit and receive the collected data. The system uses a different kind of sensors to monitor different parameter which are temperature, pH level, and turbidity of the lake on the transmitter node and send it to the receiver node where it will connect to the user$1 (Bs laptop to get the collected data from the sensors. The system also uses an artificial intelligence to predict status of the water using the parameters from the sensors. The designed system will be beneficial to the persons who live near the lake as they are much affected by the sudden change in parameter of the Laguna Lake. The artificial intelligence uses a decision tree algorithm to predict how those parameters will affect water quality on the Laguna Lake. The study aims to design a LoRa-based communication system integrated with artificial intelligence for real-time monitoring of water quality in Laguna Lake. It specifically aims to transmit and receive data from the sensors using LoRa module with low latency and use artificial intelligence to accurately predict water quality on the lake. The device has undergone a thorough budget analysis, affirming its cost-effectiveness at a total cost of PHP 4,913.00. The emphasis on simplicity in the system's design ensures that it remains accessible and user-friendly, contributing to its practicality without compromising efficiency. This cost-effective approach aligns with specified requirements for efficient rainwater harvesting, making the system not only economically viable but also easy to use and implement. Evaluation results underscore the very high acceptability of the system in terms of functional suitability, maintainability, performance efficiency, reliability, and usability. Notably, the overall weighted mean of the level of the acceptability of the system is 4.632 which describes that the system is very much acceptable.s
Thesis